English linguistic neo-imperialism in the era of globalization: A conceptual viewpoint - Zeng, Jie; Ponce, Ariel Robert; Li, Yuxin (Frontiers in Psychology, 2023)
As Phillipson warned, ‘[l]inguistic imperialism [is] alive and kicking’ and has become even more subtle in an era when English has become the global lingua franca. With this, this conceptual paper aims to propose features of linguistic neo-imperialism by describing how English has continuously spread and retained its power in various domains particularly in periphery countries, whether ex-colonies or non-colonies. Broadly, we highlight these features from the aspects of communication, business, academia, and education. The features of English linguistic neo-imperialism are interrelated and interactive in these fields, reinforcing the current dominant position of English. We then proceed with drawing implications for the local languages, particularly in their preservation and use alongside English and other dominant lingua francas.